Birth weight changes in a major city under rapid socioeconomic transition in China - Jian-Rong He (Nature Portfolio, 2017)
Abstract Estimates of trends in birth weight may be useful in evaluating population health. We aimed to determine whether temporal changes in birth weight have occurred amongst 2.3 million neonates born in Guangzhou, China, during 2001–2015 and investigate the socioeconomic determinants of any changes. Trends in mean birth weight and annualized changes with the associated 95% confidence intervals (CIs) in the incidence of small for gestational age (SGA) and large for gestational age (LGA), defined as birth weight <10th or >90th centile respectively for gestational age and sex, were examined using linear and Poisson regression models. We found that mean birth weight declined by 1.07 grams/year from 2001 to 2015. After adjustment for gestational length, the decline in birth weight was attenuated (0.37 grams/year). The incidence of both SGA and LGA significantly decreased during the study period (annual decrease of 1.6% [95% CI, 1.5% to 1.7%] for SGA, 1.6% [95% CI, 1.5% to 1.8%] for LGA). We found a narrowing of disparities in SGA and LGA incidence across different maternal educational levels and residence location. Our results demonstrate that there has been an increase in the proportion of neonates born in the healthy birth weight range in Guangzhou.